A Hybrid Trial To Trial Wavelet Coherence and Novelty Detection Scheme for a Fast and Clear Notification of the Uncomfortable Loudness Level - Mohamed Aminuddin, Mai Mariam; Mustaffa, Izadora (2011)
To determine the uncomfortable loudness (UCL) level is not an easy task, especially in children. A need to objectively measure this level is crucial as the age of hearing devices candidates is getting younger. Previous studies have shown that the feasibility of habituation correlates in late auditory evoked potentials for a measurement technique of UCL identification is promising. Nevertheless, a scheme that could provide a fast and clear notification of the UCL level is desirable. The present study has introduced a hybrid trial to trial wavelet coherence and novelty detection scheme to analyze the habituation in late auditory evoked potentials (LAEPs) i.e., relative changes within trial sequences. In 10 normal hearing subjects, a clear discrimination between 50 decibel (dB) sound pressure level (SPL) stimulated LAEPs and 100 dB SPL stimulated LAEPs. In addition, the proposed scheme is able to highlight the presence of habituation and the number of stimuli could be reduced up to 60% percent for meaningful results. Therefore, the proposed approach provides an encouraging foundation for a fast and reliable scheme in developing an objective loudness scaling measurement, in particular to determine the UCL level.